THU0051 LOW-DOSE INTERLEUKIN-2 SELECTIVELY EXPAND AND ACTIVATE REGULATORY T CELLS ACROSS 13 AUTOIMMUNE DISEASES. (2nd June 2020) - Rosenzwajg, M.; Lorenzon, R.; Cacoub, P.; Pitoiset, F.; Aractingi, S.; Banneville, B.; Beaugerie, L.; Berenbaum, F.; Champey, J.; Chazouilleres, O.; Corpechot, C.; Fautrel, B.; et al.
Abstract : Background: Regulatory T cells (Tregs) prevent autoimmunity and control inflammation. As low-dose interleukin-2 (ld-IL2) expands and activates Tregs, it has a broad therapeutic potential for any autoimmune or inflammatory disease (AIID). We performed a disease-finding "basket trial" (TRANSREG NCT01988506 ) in patients affected by one of 11 different AIID and reported the outcome of the first 46 patients ( Rosenzwajg et al, ARD 2019 ). Objectives: Here we analyzed and discussed results from deep immunophenotyping, of 78 patients, to comprehensively study the effect of ld-IL2 on the immune system of patients affected by various AIID Methods: We performed a prospective, open label, phase I-IIa study in 78 patients with a mild to moderate form of one of 13 selected AIID. All patients received ld-IL2 (1 million IU/day) for 5 days, followed by fortnightly injections for 6 months. Deep immunophenotyping was performed before and after 5 days of ld-IL2. Results: ld-IL2 significantly expands both memory Tregs as well as naïve Tregs, including recent thymic emigrant Tregs. It also activates Tregs as demonstrated by the significantly increased expression of HLA-DR, CD39, CD73, GITR, CTLA-4. Similar results were observed across the different AIID. Conclusion: ld-IL2 "universally" improves Treg fitness across 13 autoimmune and inflammatory disease. References: [1]Rosenzwajg M#, Lorenzon R#, Cacoub P, Pham HP, Pitoiset F, El Soufi K, RIbet C, Bernard C, Aractingi S, Banneville B, Beaugerie L, Berenbaum F, Champey J, Chazouilleres O, Corpechot C, Fautrel B, Mekinian A, Regnier E, Saadoun D, Salem JE, Sellam J, Seksik P, Daguenel-Nguyen A, Doppler V, Mariau J, Vicaut E, Klatzmann D. Immunological and clinical effects of low-dose interleukin-2 across 11 autoimmune diseases in a single, open clinical trial. Ann Rheum Dis. 2019 Feb;78(2):209-217. doi: 10.1136/annrheumdis-2018-214229. Epub 2018 Nov 24. Disclosure of Interests: Michelle Rosenzwajg: None declared, Roberta Lorenzon: None declared, Patrice cacoub: None declared, Fabien Pitoiset: None declared, Selim Aractingi: None declared, Beatrice Banneville Speakers bureau: Lilly, Novartis, Laurent Beaugerie: None declared, Francis Berenbaum Grant/research support from: TRB Chemedica (through institution), MSD (through institution), Pfizer (through institution), Consultant of: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Bone Therapeutics, Regulaxis, Peptinov, 4P Pharma, Paid instructor for: Sandoz, Speakers bureau: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Sandoz, Julien Champey: None declared, Olivier Chazouilleres: None declared, Christophe Corpechot: None declared, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB, Arsene Mekinian: None declared, Elodie Regnier: None declared, david Saadoun: None declared, Joe-Elie Salem: None declared, Jérémie SELLAM: None declared, Philippe Seksik: None declared, David Klatzmann Consultant of: ILTOO Pharma